SPACIAL ANALYSIS OF VIDEO SURVEILLANCE AS A TACTICAL RESPONSE TO TERRORISM AND ORGANISED CRIME TRENDS: CASE STUDY OF MADRID (Journal of the Spanish Institute for Strategic Studies, 2018)
Terrorism and organised crime are two of the most pressing threats that our societies must combat. Urban areas in western countries form the perfect environment for their growth and penetration. In this research paper, we analyse the pros and cons of CCTV systems and the role that they should play as part of a national security response. The central district of Madrid has been chosen as a laboratory for this analysis, given both its unfortunate history of terrorist acts and the continued proliferation of organised crime cells operating within the city. As a result, we have endeavoured to develop a method that guarantees the tracking of any subject/object within a predefined perimeter, using only existing infrastructure